68Ga-DOTA-DiPSMA PET/CT Imaging: Biodistribution, Dosimetry, and Preliminary Application in Prostate Cancer - Jiaying Zhang; Zefang Lin; Xiaojun Zhang; Rong Lin; Mengchao Cui; Weibing Miao; Weibing Miao; Shaobo Yao; Shaobo Yao (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose: This prospective trial aimed to evaluate the safety, dosimetry, and biodistribution of a novel theranostic probe 68Ga-DOTA-DiPSMA. Also, we have performed the first preliminary application with 68Ga-DOTA-DiPSMA in prostate cancer (PCa) patients.Methods: Five healthy volunteers and ten PCa patients were injected with an intravenous bolus of 68Ga-DOTA-DiPSMA. They received serial whole-body PET scans from the time of injection up to 60 min post-injection, with a second PET/CT scanning at 120 min post-injection. In PCa patients, low-dose CT scan and whole-body PET were performed with 2 min per bed position in 40 min post-injection. Absorbed organ doses and effective doses were calculated using OLINDA/EXM. Normal organ uptake and tumor lesion uptake were measured. A lesion-by-lesion analysis was performed.Results: 68Ga-DOTA-DiPSMA administration was safe and well-tolerated. The kidneys received the highest absorbed dose (114.46 ± 29.28 μSv/MBq), followed by the urinary bladder wall (100.82 ± 46.22 μSv/MBq) in accordance with the expected Prostate-Specific Membrane Antigen (PSMA) renal excretion of the tracer. The mean effective dose was 19.46 ± 1.73 μSv/MBq. The SUVmax of 68Ga-DOTA-DiPSMA PET/CT for PCa lesions, bone metastases, and lymph node metastases was 4.41 ± 2.72, 2.95 ± 1.11, and 3.26 ± 1.20, respectively.Conclusion: Injection of 68Ga-DOTA-DiPSMA is safe and associated with low absorbed and effective doses. 68Ga-DOTA-DiPSMA shows favorable kinetics and imaging characteristics in patients who warrant further head-to-head comparison to validate 68Ga-DOTA-DiPSMA as an alternative for gallium-68-labeled PSMA clinical PET. Low nonspecific uptake in normal organs of 68Ga-DOTA-DiPSMA indicates potential radioligand therapy (RLT) application when labeled with 177Lu, 90Y, or 225Ac.